The globalization of steam coal markets and the role of logistics: an empirical analysis - Aleksandar Zaklan; Astrid Cullmann; Anne Neumann; Christian R. von Hirschhausen (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
In this paper, we provide a comprehensive multivariate cointegration analysis of three parts of the steam coal value chain - export, transport and import prices. The analysis is based on a rich dataset of international coal prices; in particular, we combine data on steam coal prices with freight rates, covering the period December 2001 until August 2009 at weekly frequency. We then test whether the demand and supply side components of steam coal trade are consistently integrated with one another. In addition, export and import prices as well as freight rates for individual trading routes, across regions and globally are combined. We find evidence of significant yet incomplete integration. We also find heterogeneous short-term dynamics of individual markets. Furthermore, we examine whether logistics enter coal price dynamics through transportation costs, which are mainly determined by oil prices. Our results suggest that this is generally not the case.
Keywords: L11; Q41; C22; 330; Steam coal; market integration; multivariate cointegration; Kohlenmarkt; Marktintegration; Globalisierung; Außenhandel; Transportlogistik; Transportkosten; Kohle; Preis; Schätzung; Welt